Metode Mitigasi Longsorlahan di Kecamatan Gumelar Kabupaten Banyumas Provinsi Jawa Tengah - Suwarno Suwarno; Sutomo Sutomo (Forum Geografi, 2007)
This research aims to find formulating to mitigation of dangser of landslide, by observe on the classes of landslise dangser, the risk of landslide and the landslide disaster. The method used in the research is survey with two kinds of variables, the dependent variable includes the classes of dangser and the classes risk for the landslide, and the independent variable is the effart of mitigation. The classes of dangser and risk for the landslide are obfained from the secondary data, white the efforts of mitigation for the landslide are determined in accordance with the classes of landslide danser and risk landslide by considery the supporting factors. The result of the research shows that the field studied is the area with high risk of landslide. The dominant factors for the risk are the type of litology, and the weatering. The classes of landslide risk ranges from the low to the high. Hence, the efforts of mitigation should be tayseted first to those areas with the high risk of landslide. The efforts of mitigation to put into practive should consider. The dominant factors in the area, its can be underfaken by desighing a priovity, based on its terms covering shout ferm, medium term and long term.